2012
DOI: 10.1158/1541-7786.mcr-12-0296
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 Drives c-Met–Dependent Migration and Scattering

Abstract: The transmembrane mucin MUC1 is overexpressed in most ductal carcinomas, and its overexpression is frequently associated with metastatic progression. MUC1 can drive tumor initiation and progression via interactions with many oncogenic partners, including β-catenin, the epidermal growth factor receptor (EGFR) and Src. The decoy peptide PMIP (Protein transduction domain MUC1 Inhibitory Peptide) has been shown to inhibit the tumor promoting activities of MUC1 in breast and lung cancer, including cell growth and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…11, 12 Abnormal activation of c-Met has been 11 reported in many types of cancers, occurring as a consequence of gene amplification 12 or rearrangement, transcriptional regulation as well as autocrine or paracrine ligand 13 stimulation. [13][14][15][16] Importantly, overexpression of HGF and/or c-Met have been 14 associated with poor prognosis or metastatic progression. In addition, Met 15 amplification is observed in 20% of acquired resistance to EGFR inhibitors.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…11, 12 Abnormal activation of c-Met has been 11 reported in many types of cancers, occurring as a consequence of gene amplification 12 or rearrangement, transcriptional regulation as well as autocrine or paracrine ligand 13 stimulation. [13][14][15][16] Importantly, overexpression of HGF and/or c-Met have been 14 associated with poor prognosis or metastatic progression. In addition, Met 15 amplification is observed in 20% of acquired resistance to EGFR inhibitors.…”
mentioning
confidence: 99%
“…In addition, Met 15 amplification is observed in 20% of acquired resistance to EGFR inhibitors. 17 Tumor 16 micro-environment elicits innate resistance to BRAF inhibitors via HGF secretion. 18 …”
mentioning
confidence: 99%
See 2 more Smart Citations
“…87 We found that treatment with a competitive MUC1 inhibitor downregulates c-Met in breast cancer cells, and that MUC1 promotes EGFand c-Met-dependent cell motility, scattering and the formation of invasive protrusions. 88 In addition, MUC1 has recently been found to be upregulated in a subset of lung cancers which also have upregulated or constitutively active EGFR and c-Met. 89 In this study, lung cancer cell lines were analyzed for expression of genes associated with tumorigenesis, and MUC1, EGFR and c-Met expression were positively correlated.…”
mentioning
confidence: 99%